Trade Union Growth in Canada : 1911-1970 - Swidinsky, R. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1974)
This paper is primarily an attempt to isolate the determinants of trade union membership growth in Canada over the past six decades.